2019
DOI: 10.1080/19371918.2019.1666072
|View full text |Cite
|
Sign up to set email alerts
|

“The Bottle Is My Wife”: Exploring Reasons Why Men Drink Alcohol in Ugandan Fishing Communities

Abstract: Fishing communities in Uganda have high rates of excessive alcohol consumption and negative health outcomes related to alcohol consumption, such as HIV acquisition and transmission and intimate partner violence victimization and perpetration. Research lacks understanding of alcohol use in Ugandan fishing communities, underlying reasons for excessive drinking among fishermen or how their community perceives negative health outcomes linked to excessive alcohol consumption. This qualitative study was conducted am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 47 publications
2
21
1
Order By: Relevance
“…The current study found women’s occupation to be statistically significantly associated with past alcohol use, with higher odds of drinking reported among women who worked at a bar/restaurant. This finding supports our previous qualitative research in which community members narrated how women working in/around bars were more likely to use alcohol, relative to women in other professions and settings (e.g., agrarian communities) [ 22 ]. Thus, it makes sense that women in fishing areas had heightened likelihood of drinking given their tendency to do bar work and because so many men in fishing areas, many of whom were presumably the partners of women interviewed, were also drinking.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The current study found women’s occupation to be statistically significantly associated with past alcohol use, with higher odds of drinking reported among women who worked at a bar/restaurant. This finding supports our previous qualitative research in which community members narrated how women working in/around bars were more likely to use alcohol, relative to women in other professions and settings (e.g., agrarian communities) [ 22 ]. Thus, it makes sense that women in fishing areas had heightened likelihood of drinking given their tendency to do bar work and because so many men in fishing areas, many of whom were presumably the partners of women interviewed, were also drinking.…”
Section: Discussionsupporting
confidence: 87%
“…Among men in our sample, those who earned their primary income through fishing had the highest odds of past year alcohol use compared to men in the reference occupation of agriculture (aOR = 1.9, 95% CI 1.5, 2.4, p < 0.01). This builds on our previous qualitative research with residents from Rakai fishing communities who explained that fishing is the most lucrative local industry, providing ample disposable income that can be (and is) used to purchase alcohol [ 22 ] in any location. Similarly, men in fishing areas were significantly more likely to report past year alcohol use, relative to men in agrarian communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the policy and societal level, lack of enforcement of national laws to restrict alcohol use emerged as an important factor [ 58 , 60 63 , 69 ]. The authors also documented the widespread belief that “everybody drinks” and a “life is short mentality” (due to the danger of fishing activities) as key contributors to alcohol use in fishing communities [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…But in actual practice, the total sample size was 501. We aimed to sample nearly the same number of participants from each sampled district because we did not have the population sizes of the landing sites since these are highly migrant and mobile populations [ 32 ]. For the sample size calculation, we made an assumption of 50% HIV risk behavior obtained from a recent study [ 20 ], implying that p = 0.50 and q = 0.50, confidence level of 95%, error term of 10%, design effect of 2, and non-response of 5%.…”
Section: Methodsmentioning
confidence: 99%